Les minorites nationales etniques et religieuses en Bulgarie - Girard, Andre. (London)
1 mikrofilm makarası (789 poz) S.R 6/2 (poz 182-376) S.R 1/45 (poz 377-401) S.R 1/16 (poz 402-445) S.R 1/43 (poz 446-488) S.R 1/30 (poz 490-547) S.R 1/63 (poz 548-558) S.R 19/38 (poz 559-789)